SOCIAL WELFARE IN INDONESIA (A LITERATURE STUDY) - Ihil Syukur Baron (JURNAL KINDAI, 2017)
Abstract: Social welfare is not a new term issue either in global or nationaldiscourses. Since 1960’s the United Nations has addressed the issue of socialwelfare as one of activities of international community. In Indonesia, the term ofsocial welfare can be found in Law No.11 of 2009. Looking for this miserableportrait in development of social welfare it means that since Indonesiaindependence 69 years ago our country did not make any progress. According theConstitution in Indonesia, everyone has the right to adequate social welfare andhealth care services. The concrete solutions which one of them is if they can giveinsurance to their patients’ therefore they have a guarantee related their health.Keywords: social welfare, the issues, concrete solutions